Effectiveness of extracorporeal membrane oxygenation (ECMO) therapy in critically patients with COVID-19 (Research, Society and Development, 2022)
Severe cases of COVID-19 may require oxygen support therapies, such as the use of Extracorporeal Oxygenation Membrane (ECMO) and mechanical ventilation (MV). ECMO is a therapy used for temporary support in cases of pulmonary and/or cardiac function failure. This integrative review aimed to assess the scientific literature on the effectiveness of ECMO in critically patients with COVID-19. Articles collected from PubMed, published from December 2019 to June 2021, using the descriptors "COVID-19" and "ECMO" were included in this review. Articles that did not present results on the assessment of the relation between ECMO and COVID-19 and those that fell into the category of letter to the editor model or narrative reviews were excluded. For an integrated discussion, the articles were grouped in a table containing title, objective, method, methodology, results and conclusion. 36 articles were included for the integrative analysis. It was possible to evidence a greater efficacy of ECMO in younger patients (< 71 years), with greater disease severity and in those with comorbidities. However, the therapy has certain types of complications, such as a high risk of thrombosis and circuit failure, which can lead to an unsuccessful weaning from ECMO. ECMO therapy can help critically patients with COVID-19 in certain conditions, although it may increase the risk of thrombosis, and further studies are needed for better clarification.